Поделки с тиснением по бумаге - Зайцева Анна Анатольевна (Азбука рукоделия, 2009)
Экземпляры: Ч/з ДБ (20091028) / Инвентарный номер: 95468 / Цена: 84.30 / Сис.шифр: 37.248 / Авт.знак: З-17 / ГРНТИ: 75.35 / ББК: 37.24